A low-cost autonomous and scalable hydroponics system for space farming - Jae Hyeon Ryu; Jeonghyun Baek; Zarin Subah (HardwareX)
An alternative food production system using hydroponics is proposed to grow vegetables in a controlled environment that is implementable in space. The proposed system is an autonomous, modular, scalable, and soilless food production platform (ASFP) that can be installed in a spacecraft by meeting requirements and constraints set by the National Aeronautics and Space Administration (NASA). A suite of Internet of Things (IoT) sensors was used to monitor indoor climate as well as water quality in ASFP. Average values of air temperature and relative humidity in the environmentally-controlled room are maintained between 20–24 °C and 48–62 %, while water quality components, including dissolved oxygen (DO, ppm), electrical conductivity (EC, µS/m), pH, and water temperature (WT, Celsius) are monitored by the IoT sensor in real-time during the growing period. Repeated measure analysis is also performed to evaluate the plant growth performance. The result indicates that plant growth is attributed significantly to pH and EC values. A real-time data visualization and sharing platform is another avenue for the space farming ecosystem in the years to come.